Pengaruh Motivasi terhadap Hasil Belajar Siswa IPA di SMAN 6 Muaro Jambi - Wita Ardina Putri; Riska Fitriani; Endah Febri Setya Rini; Febri Tia Aldila; Tri Ratnawati (Universitas Indraprasta PGRI Jakarta, 2021)
Motivation to learn is an encouragement given by someone to others in order to achieve their goals. Weak students’ motivation can reduce students’ learning outcomes. So it can be said that learning motivation is one of the factors that can affect student learning outcomes. Hence, the purpose of this study is to discover the effect of learning, motivation on student learning outcomes in physics subjects in straight motion material at SMA N 6 Muaro Jambi.This research utilized quantitative research methods with surveys. The subjects of this study were students of class X IPA school year 2019/2020 consisting of 50 people. The instrument used was a questionnaire about motivation and multiple choice questions about straight motion material. The result obtained from this study was the learning motivation of students was classified as high or good criteria. Student learning outcomes in the physics subject matter of straight motion were in the fairly good category. Based on the regression test which aimed at determining the effect of learning, motivation on learning outcomes, it was discovered that there was a good and positive influence between motivation and student learning outcomes at SMAN 6 Muaro Jambi.